2019
DOI: 10.1016/j.dhjo.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with multiple sclerosis: A study with patients and caregivers

Abstract: Background: Multiple Sclerosis (MS) is a chronic disease that affects patients' quality of life and requires long term demanding care. Objective: The purpose of this study was to examine the relationships between patients and caregivers' variables regarding patients' quality of life, the moderating role of marital satisfaction between patients' psychological morbidity and quality of life, and the contribution of patient and caregiver variables towards patients' quality of life. Methods: The sample included 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 51 publications
2
35
0
3
Order By: Relevance
“…Although the interdependence theory and actor-partner interdependence theory [ 12 , 13 ] posit that it is important to consider the influence of shared social contexts between couples, many studies did not carefully consider the quality of shared social relationships in affecting the dyadic effects [ 8 ]. Despite the overall positive influence of marital satisfaction in diverse domains [ 7 ], the present study demonstrated that, instead of buffering the negative influence, greater marital satisfaction magnified the negative dyadic influence of health on life satisfaction in older married couples, which was consistent with some previous work [ 4 , 19 ]. For instance, Polenick et al found that relationship closeness magnified the negative association between patients’ illness severity and spouses’ well-being [ 4 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although the interdependence theory and actor-partner interdependence theory [ 12 , 13 ] posit that it is important to consider the influence of shared social contexts between couples, many studies did not carefully consider the quality of shared social relationships in affecting the dyadic effects [ 8 ]. Despite the overall positive influence of marital satisfaction in diverse domains [ 7 ], the present study demonstrated that, instead of buffering the negative influence, greater marital satisfaction magnified the negative dyadic influence of health on life satisfaction in older married couples, which was consistent with some previous work [ 4 , 19 ]. For instance, Polenick et al found that relationship closeness magnified the negative association between patients’ illness severity and spouses’ well-being [ 4 ].…”
Section: Discussionsupporting
confidence: 91%
“…Different from its generally positive direct effect on well-being [ 7 ], some studies considering the moderating role of marital satisfaction revealed that it can backfire in some health situations [ 16 , 17 , 18 ]. For instance, Santos et al found a negative association of symptoms of anxiety and quality of life only among patients with multiple sclerosis reporting higher marital satisfaction [ 19 ]. However, to our knowledge, there were no studies examining the moderating role of marital satisfaction on both actor and partner effects of disabilities simultaneously on life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…On average, MS affects women two to three times more often than men. [5,6]. There are four forms of MS, the most common of which are relapsing-remitting MS (RRMS, 85%) and primary progressive MS (PPMS, 10%).…”
Section: Introductionmentioning
confidence: 99%
“…Debska et al [24] and Yamout et al [26] found a connection between the social support and the QoL of the MS patients. Santos et al [31] studied the contentment in marriage and confirmed that it impacts the anxiety of the patients and mental QoL.…”
Section: Discussionmentioning
confidence: 98%
“…Less attention is paid to the QoL of the family members [30] or at the same time to the MS patients and their caregivers [24, 31]. For this reason, we focused on both groups.…”
Section: Introductionmentioning
confidence: 99%